Are contracts concluded on the Internet valid and enforceable ? An analysis of the Law applicable to contracting on the Internet - Archbold, Craig (Department of Private Law, 2021)
The Internet allows contractual negotiations to take place electronically between parties in different national and international jurisdictions. A commercial transaction may be concluded and performed electronically without the parties ever having met or communicated with each other in a formal or informal manner. It is a unique technology that may resemble an instantaneous telex in certain instances, and therefore, may invoke prima facie comparisons to the legal principles relating to telephonic or telex communication. However, in other instances the medium resembles a conventional post box, an analogy that immediately invokes the expedition theory.